Interference of volunteer corn on soybean cultivars growth and yield - Caratti, Fernanda Cassiane; Lamego, Fabiane Pinto; Bianchi, Mario Antonio; Farias, Humberto; da Silva, Bruno Moncks; Cechin, Joanei (Comunicata Scientiae, 2019)
Spontaneous corn plants in soybean crop are considered weeds because they compete for the same environmental resources. The objective of this study was to evaluate the competitive ability of soybean cultivars when in coexistence with spontaneous corn plants. A field experiment was conducted in CCGLTEC, Cruz Alta/RS, in 2014/15, in a split-plot design, with the main plot being composed of four different cultivars (CD 2694, BMX 7166, TEC 5718, TEC 6029) and the subplots of interference conditions (without the presence of corn volunteer plants, in the presence of corn until the V3, V6, V9 stages, or for the entire soybean cycle. Leaf area, shoot dry mass, plant height, chlorophyll index, and development stage were determined at 15, 30, and 49 DAE; we also determined apparent biological productivity, apparent harvest index, and components of productivity and grain yield. The cultivars showed losses in leaf area and shoot dry mass when in coexistence with corn (8 plants m-2) in the three periods evaluated. All cultivars showed losses in apparent biological productivity, apparent harvest index, and final grain yield when growing under competition throughout the cycle. Cultivars with a medium/long growth cycle, such as CD 2694 (maturity groups (GM): 6.9) and BMX 7166 (GM: 6.6), show a higher competitive ability up to V9 stage in contrast to cultivars with a short cycle, such as TEC 5718 (GM: 5.9) and TEC 6029 (GM: 5.7).